Determinan Pengungkapan Aset Biologis (Studi Empiris pada Perusahaan Agriculture yang Terdaftar di Bursa Efek Indonesia - Viona Azzahra; Elvira Luthan; Amy Fontanella (Universitas Batanghari Jambi, 2020)
Disclosure of biological assets in agricultural companies has been ratified in 2018, which is about PSAK 69. This standard requires agricultural sector companies to provide disclosures about their biological assets. Several studies have been carried out by previous studies. However, studies in Indonesia are still limited. Therefore, there is a desire to investigate this phenomenon. The purpose of this study is to examine the influence of what factors influence the disclosure of biological assets. The population in this study are all agricultural companies listed on the Indonesia Stock Exchange for 2015-2018. The final sample in this study were 50 companies obtained using the purposive sampling method. Data were analyzed using multiple regression analysis. The results of this study indicate that the intensity of biological assets, Public Ownership, Audit Committee Meetings have a positive influence on the disclosure of biological assets.